2019
DOI: 10.7567/1347-4065/ab00f0
|View full text |Cite
|
Sign up to set email alerts
|

Computer simulation for electrochemical impedance of a living cell adhered on the inter-digitated electrode sensors

Abstract: The sensitivity of inter-digitated electrode (IDE) impedance sensors for adherent cell monitoring is investigated by computer simulation. Governing equation based on Maxwell’s equation is solved using finite element method by a commercially-available software to obtain impedance with/without living cells on sensor surface. For IDE, the current concentration is shown to be higher along the edges, as a result of which the electrode edges have a higher impact on impedance. The higher sensitivity is observed in ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…We observed that the sensitivity increased with the increase in the number of electrode fingers (N) validating the results from our previous report. 32) It was also found that the peak sensitivity corresponding to W/S < 1 and W/S > 1 exhibited higher sensitivity than W/S = 1. Moreover, the slope in the range of W/S < 1 showed the larger increase in sensitivity.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…We observed that the sensitivity increased with the increase in the number of electrode fingers (N) validating the results from our previous report. 32) It was also found that the peak sensitivity corresponding to W/S < 1 and W/S > 1 exhibited higher sensitivity than W/S = 1. Moreover, the slope in the range of W/S < 1 showed the larger increase in sensitivity.…”
Section: Introductionmentioning
confidence: 91%
“…[25][26][27] In addition to this, there are quite a few reports that address the factors influencing the sensitivity of IDE in the absence of living cells. [28][29][30][31] Meanwhile, these issues were addressed in our previous report 32) where the sensitivity due to IDE geometry was studied in the presence of adherent cell through 3D computer simulations. However, the sensitivity study was limited to the electrode geometry where the width (W) of the electrode was equal to the spacing (S) in the presence of adherent cell.…”
Section: Introductionmentioning
confidence: 99%
“…Double-layer capacitance per unit area 46) F m 2 -0.89 Solution relative permittivity 47) 78 Solution conductivity 47) S m 1 -1.5 Cell membrane thickness 46) nm 5.0 Cell membrane relative permittivity 46) 5.0 Cell membrane conductivity 48) S m 1 -1.0 10 9…”
Section: Parameter Unit Valuementioning
confidence: 99%
“…Table 1 shows the parameters used for the simulation, where almost all of the values were based on the literature of Sun et al 26 The double layer capacitance per unit area was a calculated value. 22 This study focuses on cell density and thus the cytoplasm conductivity was set to be same as that of the solution. The simulations were performed with various electrode coverage of cells existing between PFE.…”
Section: Finite Element Simulation Of Impedance Dependence On Adherenmentioning
confidence: 99%
“…27 The spherical cell diameter was 10 m and adhesive cell diameter and height were 10 m and 5 m, respectively. 22 The cell nucleus within the cell was ignored because it does not affect the R gap depending on the extracellular ion conduction. The top and bottom faces of the model domain were defined as working electrode (WE) and counter electrode (CE), respectively.…”
Section: Finite Element Simulation Of Impedance Dependence On Adherenmentioning
confidence: 99%